How Does Internet Finance Influence the Monetary Policy? Evidence from China - Rathnayake, Dilesha Nawadali; Dan, Jiang; LouembÃ©, Pierre Axel; Yvanna, Otek Ntsama Ursule (International Journal of Economics and Financial Issues, 2021)
Chinese banks have gradually expanded their financial services into overseas financial services and financial trade transactions. The financial services system is becoming more and more humanized and intelligent with the global economy’s rapid development and progress. It improves the quality of banks’ financial services and plays a vital role in its financial system construction and financial product innovation. As an internal driving force for the development of the financial industry, financial innovation has a vast and extensive impact on the economy. Because of the importance of monetary policy on national macroeconomic regulation and control, it is of great practical significance to study the impact of financial innovation on monetary policy effectiveness. This paper has conducted an in-depth analysis of the core concepts of internet finance, and suggestions and policy implications are given to improve China’s monetary policy’s effectiveness. Keywords: financial products, service innovation, monetary policy, effectiveness analysis JEL Classifications: G29, G14 DOI: https://doi.org/10.32479/ijefi.11007